Financial Analyst Work Papers to Analysis Insurance Types Affection in Islamic Bank (Jordanian Islamic Bank Case Study) - Nazal, Abdullah Ibrahim (Asian Journal of Social Sciences and Management Studies, 2016)
This study is one of very few studies which have investigated the insurance types in the Islamic banks with case study. It explains the need to make financial analysis work papers up to the Insurance types to give fair report. The study finds that there are three Insurance types in Jordanian Islamic Bank which are: Islamic Insurance Company, Tabaduly Insurance Box, and Facing Sharing Investment Risk Box. There is relationship between these types in Jordanian Islamic bank. Every type has way of accounting and way of reduce risk also it has different Place in financial tables up to deferent Fiqh original type and resources of Law. There is need to build suitable financial analysis work papers which show the different of accounting and different of added value than Traditional banks and traditional Insurance companies. Searcher recommended suggestion up to Forth steps to get fair report which is to find resource of investigation, to be sure accounting must meet law, to build paper works up to insurance types, and to use the doubt rule.